PENYULUHAN COVID-19 DAN PENERAPAN PROTOKOL KESEHATAN DI KALANGAN SEKOLAH - Herviani Sari; Firdaus Fahdi; Hengky Frengki Manulang; Herawati Bukit; Stefani Anastasia Sitepu; Erlina Hayati (INSTITUT KESEHATAN DELI HUSADA, 2021)
At the end of 2019, the world was shocked by the emergence of a new virus from Wuhan, China. The virus is known as nCoV (novel corona virus). This virus is a new variant of the corona virus that broke out in 2002 which is known by people as SARS (Severe Acute Respiratory Syndrome). Then this new type of corona virus was known as SARS-CoV-2 and the name of the disease was known as COVID-19. According to reports until March 2020 the SARS-CoV-2 virus has infected 90,308 people in China and the death rate has reached 3,087 people. COVID-19 was detected in Indonesia for the first time in early March 2020. The rate of spread of COVID-19 was very fast within a few months, the number of positive patients with COVID-19 in August 2020 reached 172,053 cases. COVID-19 is very contagious and spreads quickly, so to avoid COVID-19 it is necessary to do 3M (wear a mask, keep your distance and wash your hands). Because it has been months but the plague has not ended, the whole world has begun to take a stand to initiate new policies in people's daily lives. This policy is known as the New Normal Era.